Treatment of gastric bleeding of ulcerative etiology. - Rayimov G.N; Kholmukhamedov J.R; Kholmatov K; Nematjonov B. (Zien Journals, 2022)
In the Department of Emergency Abdominal Surgery of the Fergana branch of the Republican Scientific Center for Emergency Medical Care (RSCEMC), in the period from 2019 to 2021, 130 patients with gastric ulcer complicated by bleeding were operated on. Along with the generally accepted diagnostic and therapeutic methods, the methods developed in the clinic are presented. The introduction of the proposed diagnostic and treatment complex will improve the results of surgical treatment of patients with peptic ulcer
Keywords: Stomach Ulcer; Bleeding; Morphology; Treatment